PRODUCTION OF BIOETHANOL FROM BANANA PEEL (Musa paradisiaca l.) USING SULFURIC ACID CATALYST - Zulnazri Zulnazri; Arif Maulana; Agam Muarif; Novy Sylvia; Rozanna Dewi (Jurnal Teknologi Kimia Unimal, 2023)
.Bioethanol is a pure alcoholic compound consisting of ethanol and is produced through a biomass fermentation process with the help of microorganisms.  Making bioethanol can be done using plants that contain starch, carbohydrates, glucose, and cellulose. One option is kepok banana peels.  Utilization of kepok banana peels can increase the variety of raw materials for bioethanol production which are cost-effective and easy to obtain.  This research has been done before, what has never been done is the manufacture of bioethanol using various catalysts H2SO4, hydrolysis temperature and fermentation time.  This research method uses hydrolysis, fermentation and distillation with variations in hydrolysis temperatures of 80°C, 90°C and 100°C, variations in catalyst concentration H2SO4 1 M, 2 M, 3 M with fermentation times of 5, 7, 9 days. Results of this study  the highest yield and density were obtained at the hydrolysis temperature of 90°C, the catalyst concentration of 3 M H2SO4 with a fermentation time of 9 days was 5.0432% and 0.8346 gr/ml, and the highest bioethanol content was at the hydrolysis temperature of 90°C, the catalyst concentration  2 M H2SO4 with 9 days fermentation time of 0.2884%.  The size of a grade is influenced by the length of time of fermentation and the amount of catalyst given.  The density value of the bioethanol obtained meets the Indonesian National Standard.  The results of the GC (Gas-Chromatography) test based on the highest glucose content and fermentation time at each temperature variation showed that the bioethanol content with a glucose content of 5.2%, 12.2% and 14.1% respectively at a hydrolysis temperature of 80°C  , 90°C and 100°C with catalyst concentration H2SO4 3 M and a fermentation time of 9 days, namely 1.783%, 4.024% and 5.030%.  The greater the catalytic agent used, the greater the level of glucose produced and the longer the fermentation period given, the more optimal the product will be.